"CYBERMARKETING" ALTERNATIVE MARKETING STRATEGY AND COMPETITIVE CASE STUDY IN. DYVIATECH MEDIATAMA "SANUR BOOK STORE ON-LINE" - Zakaria Zakaria; Susi Wagiyati, SKom, MM Susi Wagiyati, SKom, MM (Jurnal Sistem Informasi, 2000)
Success in business is often synonymous with success in doing selling, so businesspeople often try new breakthroughs to market its products. One of the new marketingalternative is to use telecommunications technology which is currently growingrapidly, by conducting marketing activities on-line on the internet network calledCybermarketing.Internet now has become quite warm conversation burden, both in the mass media orsociety. This is due to the technological advances in telecommunications computershas brought a huge impact on almost all parts of community life, especially business.The first is to enhance business communication, management information systemsdevelopment, until the establishment of a Virtual Organization. And the second is theutilization of Cybermarketing, such as pairing an ad on the internet, to performtransactions on-line sales of so-called electronic commerce.In this work investigated how the use of Cybermarkating for businesses in Indonesia,by making the business environment analysis in PT. Dyviatech Mediatama, which inturn can be formulated effective marketing strategies in online markets.PT Dyviatech Mediatama trying to pioneer the use of Cybermarketing that have notbeen developed in Indonesia, with the opening of Sanur, on-line book stores. Throughthe web site of Sanur on-line book store, retail services company offering books online.The pages of Sanur webs like a storefront in a book shop. Customers simply turnon the computer, access the address book in Sanur and selecting the virtual racksfound on the web pages of Sanur. When you find the books you are looking for,customers enter them into the virtual shopping bag and ordered the book through acomputer on the spot. Payment can be done using a credit card, check or accounttransfer. Then the books purchased will be delivered by courier to the address of thebuyer.Considering the development of on-line market in the future, then marketing on-lineor Cybermarketing can be used as an alternative marketing to improve salesperformance, and become one of the strategies to compete both locally and globally,in the future. Therefore, it is time for business research institutions to start doingresearch or studies related to on-line marketplace which will be used by the businessworld.